The Dynamics of Elderly Family Interaction in Krajan, Glawan Village, Pabelan Subdistrict, Central Java, Indonesia - Sri Suwartiningsih (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
Krajan subvillage is one of the areas within Glawan Village, Pabelan Subdistrict, Semarang Regency. It has a population of elderly individuals aged over 75, totaling more than 5 people. Some of these elderly individuals live alone, while others reside with their children or grandchildren. The elderly engage in various forms of interaction, such as walking to their children or grandchildren's homes. Some have their offspring visit and assist with tasks like washing clothes and sweeping the floor, occurring at least twice a week for those living alone. In this digital age, the elderly also use phones for communication and interaction with their children and grandchildren. The dynamics of social interaction take place both offline and online through phone calls, not just via messaging apps. The elderly have developed habits of interacting with their families and continue to engage with the community in various activities like communal work, traditional rituals, mourning ceremonies, weddings, births, and more.